Recycling of iron oxide waste by carbothermic reduction to utilize in FDM 3D printing materials - DOUNGKEAW, Korbkaroon; SUTTIPONG, Peeraphat; KUNGWANKRAI, Phachai; MUENGTO, Suksan; THAVORNYUTIKARN, Boonlom; TUNGTRONGPAIROJ, Jennarong (Journal of Metals, Materials and Minerals, 2023)
Iron oxide scale generally forms on low-carbon steel surfaces during the hot rolling processes and produces as solid waste more than 100 thousand tons per year. The utilization of the iron oxide scale is one possible way to reduce the production cost for steel plants and promote environmental protection. Acrylonitrile-Butadiene-Styrol-Copolymer (ABS) is widely used as engineering plastic for automotive parts because of its high strength and wear resistance. The recycling of iron oxide waste as reinforcement particles for enhancing the tensile strength of ABS composite was studied. The iron oxides were recycled by carbon powder at a high temperature between 1150℃ to 1350℃ up to 120 min. After the reduction process, the reduced iron from an optimal condition with the iron-rich fraction was ground to powder. Afterward, the 0.3 vol% to 1.3 vol% powders were mixed with ABS polymer powder and formed as composite filaments for additive manufacturing (FDM 3D printing). The tensile strength of pure ABS filament increased to 37.16 ± 2.37 MPa when added recycled iron powders. The regular distribution and 13.68 ± 9.78 µm of recycled-iron particle sizes on the ABS matrix were investigated and correlated to the mechanical properties.